Traditional usages of some medicinal plants for pediatric diseases - Sarı, Fatma; Kültür, Şükran; Koçyiğit, Mine (University of Ankara, 2023)
Objective: Different types of pediatric diseases negatively affect the lives of many people, physically. Here, we aimed to document some medicinal plants used as traditional folk medicine in pediatrics treatment. Result and Discussion: 117 taxa and 53 families have been identified as traditional herbal medicines used in defined pediatric diseases. The most frequently used medicinal plant species according to the number of citations Foeniculum vulgare Mill., Juglans regia L., Dryopteris filix-mas (L.) Schott, Rosa canina L., Mentha x piperita L., Matricaria chamomilla L. All findings are expected to form the basis for new pharmaceutical products and become a handbook for healthcare professionals.

Amaç: Çocuk hastalıklarının farklı türleri birçok insanın yaşamını fiziksel olarak olumsuz etkilemektedir. Burada geleneksel halk hekimliği olarak pediatri tedavisinde kullanılan bazı şifalı bitkileri belgelemeyi amaçladık. Sonuç ve Tartışma: Tanımlanmış çocuk hastalıklarında kullanılan geleneksel bitkisel ilaçlar olarak 117 takson ve 53 familya tespit edilmiştir. Atıf sayılarına göre en sık kullanılan tıbbi bitki türleri Foeniculum vulgare Mill., Juglans regia L., Dryopteris filix-mas (L.) Schott, Rosa canina L., Mentha x piperita L., Matricaria chamomilla L. Tüm bulguların yeni farmasötik ürünler için temel oluşturması ve sağlık profesyonelleri için bir el kitabı olması bekleniyor.
Çocuk hastalıklarında geleneksel olarak kullanılan bazı bitkiler
Keywords: Ethnobotany; Medicinal Plants; Pediatric Diseases; Traditional Medicine; Turkey; Etnobotanik; Tıbbi Bitkiler; Çocuk Hastalıkları; Geleneksel Tıp; Türkiye